Late Sodium Current of the Heart: Where Do We Stand and Where Are We Going? - Balázs Horváth; Norbert Szentandrássy; János Almássy; Csaba Dienes; Zsigmond Máté Kovács; Péter P. Nánási; Tamas Banyasz (MDPI AG, 2022)
Late sodium current has long been linked to dysrhythmia and contractile malfunction in the heart. Despite the increasing body of accumulating information on the subject, our understanding of its role in normal or pathologic states is not complete. Even though the role of late sodium current in shaping action potential under physiologic circumstances is debated, it's unquestioned role in arrhythmogenesis keeps it in the focus of research. Transgenic mouse models and isoform-specific pharmacological tools have proved useful in understanding the mechanism of late sodium current in health and disease. This review will outline the mechanism and function of cardiac late sodium current with special focus on the recent advances of the area.